PENGARUH KUALITAS PELAYANAN DAN POTONGAN HARGA TERHADAP KEPUASAN PELANGGAN KIP STORE KOTA BENGKULU - Taufik, Ahmad (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This research aims to find out the effect of service quality and price discounts on customer satisfaction at the Kip Store in Bengkulu City. This type of research uses quantitative descriptive research methods. The population used in this research were consumers from the KIP Store in Bengkulu City. The number of respondents in this study was 110 people. The data collection method uses a questionnaire and uses analysis techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the form of the regression equation Y= 3.055 + 0.366 X1 + 0.109 6.765 > 1.982) and (sig α = 0.000 < 0.005). This means H_0 is rejected and H_a is accepted. Price discounts have a significant effect on customer satisfaction, this is proven by the results of the t test showing the value of t-count > t-table (3.080 > 1.982) and (sig α = 0.000 < 0.005). This means H0 is rejected and Ha is accepted. Service Quality (X1) and Price Discounts (X2) simultaneously have a significant effect on Customer Satisfaction (Y) at the KIP Store in Bengkulu City, this is proven by the F test showing the value of f-count > f-table, namely (25.172 > 3.08 ) and (sig α = 0.000 < 0.005). This means H0 is rejected and Ha is accepted.Keywords : Service Quality, Price Discounts, and On Customer Satisfaction.